The future of war a history - Freedman, Lawrence (New York Public Affairs, 2017)
Questions about the future of war are a regular feature of political debate, strategic analysis, and popular fiction. Where should we look for new dangers? What cunning plans might an aggressor have in mind? What are the best forms of defense? How might peace be preserved or conflict resolved?
Includes bibliographical references (pages 289-361) and index.
Keywords: War--Forecasting.